Kontroversi Kurikulum Pesantren dan Tantangan dalam Membangun Standar Mutu Pendidikan : Menemukan Keseimbangan antara Tradisi dan Modernisasi - Ahsan, Muhammad Nur (Universitas Islam Negeri Walisongo, 2024)
The Islamic boarding school curriculum is considered not to suit the demands of the modern world. There are also challenges for Islamic boarding schools to improve the quality standards of their education. This research aims to determine curriculum design and improve the quality standards of Islamic boarding school education in achieving a balance of tradition and modernization. The research uses a qualitative approach with the literature study method. Data collection techniques use document studies in the form of journals, books and other sources. Data analysis uses content analysis. Research findings show that there is educational curriculum controversy and challenges to quality standards in Islamic boarding schools. Several solutions were found, namely: Development of an integrated and interdisciplinary curriculum, teacher training and development, use of technology in education, collaboration with other Islamic education institutions, and continuous evaluation. This solution must be implemented with the principle of continuity and change.